A new approximation method for common fixed points of a finite family of generalized asymptotically quasinonexpansive mappings in banach spaces - Suthep Suantai (2018)
We introduce a new iterative scheme to approximate a common fixed point for a finite family of generalized asymptotically quasinonexpansive mappings. Several strong and weak convergence theorems of the proposed iteration in Banach spaces are established. The main results obtianed in this paper generalize and refine many known results in the current literature. © 2010 Pornsak Yatakoat and Suthep Suantai.